2021
DOI: 10.1177/10105395211025901
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health and COVID-19: Policies, Guidelines, and Initiatives from the Asia-Pacific Region

Abstract: The COVID-19 outbreak was declared a pandemic by the World Health Organization in March 2020 due to rapid intercontinental spread and high morbidity and mortality. Globally, the disease has had a major impact on human lives, including health, economic, employment, psychological, and overall well-being. The COVID-19, besides causing respiratory, neurological, and cardiovascular diseases, has had significant impact on mental health. Major mental health disorders, including depression, anxiety, and stress, have r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Tourism-dependent communities were thus chosen as the key population of interest in this study because we were aware that most tourism employees and business-owners had faced significant financial losses, and we wanted to see if this corresponded with declines in their overall wellbeing. Certainly it would be easy to assume that, given the Pacific's heavy dependence on the international tourism industry, and the sustained absence of this industry over a two year period, people's wellbeing in these countries would be at an all-time low (Kumar & Patel, 2022;Samy et al, 2021). However, the research findings herein, based on a survey conducted between October 2021 and January 2022, suggest almost the opposite.…”
Section: Introductionmentioning
confidence: 76%
“…Tourism-dependent communities were thus chosen as the key population of interest in this study because we were aware that most tourism employees and business-owners had faced significant financial losses, and we wanted to see if this corresponded with declines in their overall wellbeing. Certainly it would be easy to assume that, given the Pacific's heavy dependence on the international tourism industry, and the sustained absence of this industry over a two year period, people's wellbeing in these countries would be at an all-time low (Kumar & Patel, 2022;Samy et al, 2021). However, the research findings herein, based on a survey conducted between October 2021 and January 2022, suggest almost the opposite.…”
Section: Introductionmentioning
confidence: 76%
“…For instance, Sasaki et al [ 121 ] reported that, following the evidence based on pre-disaster preparedness adopted in Japan for earthquakes and tsunamis, investing in preventive instrumental and emotional support might be beneficial to mitigate the onset of mental disorders in the case of traumatic events. Moreover, Samy et al [ 85 ] described a series of health protocols implemented in Asian countries to provide psychological support and establish a strategic plan for guaranteeing mental health services, even during extended domestic isolation or with reduced accessibility to hospitals. The need to find short-term solutions to buffer the critical pandemic situation has led to the adoption of hybrid interventions and the reinforcement of telemedicine, activating, for instance, 24/7 phone helplines [ 80 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 As per the government’s National Strategic Plan for Mental Health 2020–2025, there is no school children specific mental health catch up policy during the pandemic. While the Ministry of Health has published a guideline titled “COVID-19 Mental Health Kit—In Hospital Setting and Quarantine Centre”, it is exclusively for patients and health care workers ( Samy et al, 2021 ). In general, there is a lack of availability of child- and adolescent-friendly multidisciplinary care for mental health conditions in Malaysia ( UNICEF, National Institutes of Health Malaysia, Burnet Institute, 2022 ).…”
Section: Introductionmentioning
confidence: 99%